The Effect of Institutional Affiliation and Career Patterns on (De)centralization Preferences in Advanced Multi-Level States: Parliamentarians' Support for (De)Centralization in Belgium. Issue 2 (28th June 2020) - Dodeigne, Jeremy; Niessen, Christoph; Reuchamps, Min; Sinardet, Dave
Abstract: The decentralization of political power towards subnational entities is one of the major contemporary processes of territorial transformation in European democracies. Traditionally, research has focused on arguments related to nationalism and identities. Later, the strategic agency of political parties has been integrated as they typically play a major role in negotiating constitutional reforms. We investigate two institutionalist factors to explain why political Parliamentarians (MPs) favour decentralization while others oppose it: their parliamentary institutional affiliation and their career pattern (as well as the interaction between both). The importance of these factors is studied based on a large-scale survey among Belgian MPs from all federal and regional parliaments. Our results indicate that MPs' preferences for decentralization significantly differ depending on their institutional affiliation (regional MPs being more decentralist than national MPs). This difference is moderated by MPs' career pattern, but only for national MPs (who are more decentralist when they have a regional career pattern).